Human Leptospirosis Caused by a New, Antigenically Unique Leptospira Associated with a Rattus Species Reservoir in the Peruvian Amazon - Matthias, Michael A.; Ricaldi, Jessica N.; Cespedes, Manuel; Diaz, M. Monica; Galloway, Renee L.; Saito, Mayuko; Steigerwalt, Arnold G.; Patra, Kailash P.; Ore, Carlos Vidal; Gotuzzo, Eduardo; Gilman, Robert H.; Levett, Paul N.; et al. (PLOS Neglected Tropical Diseases, 2008)
Author SummaryLeptospirosis has emerged as a globally important infectious disease. Its impact on public health is often difficult to determine, sometimes because of low clinical suspicion, or, as is more common, difficulty in laboratory diagnosis. Gold-standard serology-based diagnosis has a number of important limitations, including the need to use live leptospires that have a sufficient diversity of antigens to be able to detect specific anti-leptospiral antibodies; such antigens vary greatly from region to region. In this paper, we report the discovery of a new species of Leptospira in the highly biodiverse region of the Peruvian Amazon, and demonstrate that the animal source of infection for humans is the domestic rat. Detailed biological characterization of this new species shows that it is antigenically unique and represents a new serogroup and serovar, proposed as Leptospira licerasiae serogroup Iquitos serovar Varillal. Incorporation of this new isolate into serological testing of patients presenting with acute febrile illness in Iquitos, Peru, showed a far higher incidence of leptospirosis than previously suspected, showing the important of using region-specific Leptospira in diagnosis. The field-to-laboratory approach presented here has general application to the discovery of other emerging pathogens and their impact on human health.